Pengembangan Suplemen Bahan Ajar pada Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) Kelas V Materi Daerahku Kebanggaanku Berbasis Kearifan Lokal Kalimantan Barat di SD Negeri 17 Pontianak Kota - Pratama, Elta Wiadria; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda; Kresnadi, Hery; Pranata, Rio (ARZUSIN, 2025)
This research aims to develop a supplement product for teaching materials based on local wisdom in West Kalimantan for class V elementary schools that is suitable for use to assist learning activities in the independent curriculum. The research method used in this research is the Research and Development (RnD) method by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data sources for this research were 27 students in class V B of the 17 Pontianak City Elementary School, 1 class teacher, 2 expert validators who assessed 3 aspects, namely material aspects, design and language aspects. The data collection techniques used in this research used interview and questionnaire techniques. The research results show that the development of teaching material supplements based on local wisdom in West Kalimantan has gone through 4 research stages and 5 research stages. The product validity results for the material aspect obtained 0.92 with the criteria (Very High Validity). Then the language aspect obtained 0.90 with the criteria (Very High Validity). Then the design aspect gets a score of 1 with the criteria (Very High Validity). The teacher response results obtained very good criteria with an average percentage score of 93.3%. The results of student responses in the first stage of the trial obtained a percentage value of 93% and the second stage of the trial obtained a percentage value of 94.4% with very feasible criteria.